Efficacy of Initial vs. Delayed Photodynamic Therapy in Combination With Conbercept for Polypoidal Choroidal Vasculopathy - Sun, Zuhua; Gong, Yuanyuan; Yang, Yating; Huang, Ying; Yu, Suqin; Pei, Junqing; Lin, Bing; Zhou, Rong; Li, Yingzi; Li, Yumin; Zhang, Junyan; Liu, Xiaoling (Frontiers in Medicine, 2022)
Purpose To compare the efficacy of initial vs. delayed photodynamic therapy (PDT) in combination with intravitreal injection of conbercept (IVC) for polypoidal choroidal vasculopathy (PCV). Design Multicenter, randomized, non-inferiority clinical trial. Subjects Naïve PCV patients. Methods Patients were randomized 1:1 into two groups: initial PDT with IVC and delayed PDT with IVC. At baseline, patients in the initial combination group were treated with PDT and IVC within 1 week, while patients in the delayed combination group were treated with IVC alone. PDT and IVC was given PRN during the follow-up in each group. Main Outcome Measures Non-inferiority of delayed PDT with IVC to initial PDT with IVC for mean change in best-corrected visual acuity from baseline to month 12 (95% CI of the difference entirely above −5 letters). Results Eighty-six patients were enrolled, with 43 in each group. At month 12, the change of BCVA in initial combination group was equivalent to that in the delayed combination group, with gains of 6.42 ± 1.89 and 7.49 ± 2.14 (mean ± standard error) letters, respectively [delayed group minus initial group: 1.07 letters; 95% confidence interval (CI): −4.62 to 6.76; Pnon−inferiority = 0.0198]. The rates of complete polyp regression were 66.67 and 45.83% in the initial and delayed combination groups, respectively. The difference was not statistically significant (P = 0.386). The mean reductions of CRT were 204.77 ± 28.79 and 84.14 ± 30.62 μm in each group respectively. The difference was statistically significant (P = 0.005). In addition, the mean injection numbers were 3.47 ± 2.39 and 4.91 ± 2.65 in each group respectively. The differences were statistically significant (P = 0.010). Conclusions There was effective in both groups in patients with PCV. The initial combination group showed a more efficient decrease in CRT and polyp regression, along with fewer injections. However, the delayed combination group was non-inferior compared with the initial combination group in terms of the improvement of BCVA. Trial Registration https://ClinicalTrials.gov, Identifier: NCT02821520.